PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA MELALUI DISIPLIN DAN SEMANGAT KERJA KARYAWAN PADA PT. BANK JATIM, Tbk CABANG JEMBER - Tatit Diansari Reskiputri; Purnamie Titisari; Isti Fadah (RELASI : JURNAL EKONOMI, 2016)
This research aims to analyze and understand and prove Empirically influence directly and indirectly working environment and compensation to job satisfaction employees through work discipline and working spirit at PT. Bank Jatim, Tbk Jember Regency. This research classified as exsplanatory reseach and confirmatory research at once with loading technique samples proportional sampling. Data acquisition will be done with questionnaires distribution directly and indirectly from respondents the PT. Bank Jatim,Tbk Jember Branch Office employee. Data that was recieved by processed by using analysis of path analysis with IBM SPSS AMOS 20 software. The results showed that the work environment, compensation, work discipline and morale has a positive and significant impact on   job satisfaction of employees. In addition the research also shows that the work environment, compensation and working discipline has a positive and significant impact on job satisfaction of employees through morale